American Consumerism of the 1950s and the Beat Generation - Bičišťová, Barbora (Univerzita Pardubice, 2020)
This paper focuses on the rise of consumerism in the United States in the fifties and on the events that were most influential concerning the development of causes. It further presents the most typical expressions of material tendencies in consumers. The main aim of this paper is the identification of these expressions in the work of Lawrence Ferlinghetti and Gregory Corso and their attitude towards the material values of the consumer society.
Americký konzumerismus 50. let a Beat Generation
Keywords: consumerism; consumption; materialism; Beat Generation; Corso, Gregory; Ferlinghetti, Lawrence; mass production; society; USA; 1950s; konzumerismus; spotřeba; materialismus; Beat Generation; masová produkce; společnost; USA; padesátá léta